Students' out-of-school science-related experiences and their level of learning interests in science - Sumbilla, Cristie S (University of the Philippines Visayas, 2019)
This study was undertaken to determine the correlation between studnets' level of out-of-school science-related experiences (OSSRE) and their level of learning interests in Science (LIS) in the selected public secondary schools in the province of Iloilo, Philippines. It also sought to determine the difference in the level of OSSRE and level of LIS when classified according to sex and socio-economic class. The International Relevance on Science Education (ROSE) questionnaire-a 169-item test, was used to assess the levels of OSSRE and LIS. The instrument adopted was validated by an international panel and was pilot tested. Using stratified random sampling, a total of 740 respondents were identified from four congressional districts. Descriptive and inferential statistics were used to analyze the data. the finding revealed that, on the average, the grade 10 students of the selected public secondary schools in the province of Iloilo registered a high level OSSRE. The results showed that the students' exposure to out-of-school activities through indirect and informal means have enriched their experiences in Science. There were significant differences in the students' level of OSSRE when the respondents were grouped according to sex and socio-economic class. As regards the level of LIS, there was a general interested level in all the Science topics among the students. Students were interested in learning about almost all of the listed topics in the questionnaire. When group according to to sex, there was no significant difference between levels of LIS. Boys are as interested with girls in learning Science topics. When grouped according to socio-economic class, there was a significant difference in student's' level of LIS. The results showed that students belonging to higher socio-economic class have higher level of LIS. The Spearman's rank-order correlating revealed that there was a significant moderate positive correlation between OSSRE and level of LIS. Thus, the more the student exposed to the out-of-school Science-related activities, the higher would be his interest in learning Science..